2015
DOI: 10.2147/ijn.s80502
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized self-assembling peptide improves INS-1 β-cell function and proliferation via the integrin/FAK/ERK/cyclin pathway

Abstract: Islet transplantation is considered to be a curative treatment for type 1 diabetes mellitus. However, disruption of the extracellular matrix (ECM) leads to β-cell destruction and graft dysfunction. In this study, we developed a functionalized self-assembling peptide, KLD-F, with ECM mimic motifs derived from fibronectin and collagen IV, and evaluated its effect on β-cell function and proliferation. Atomic force microscopy and rheological results showed that KLD-F could self-assemble into a nanofibrous scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…INS‐1 cells (No. CRB‐130515) were purchased from Saiqi Biological Engineering Co., Ltd. (Shanghai, China) and cultured in RPMI‐1640 medium containing 11.1 mmol/L glucose supplemented with 10% fetal bovine serum (FBS), 100 U/ml penicillin, 100 μg/ml streptomycin, 10 mmol/L HEPES, 2 mmol/L l ‐Glutamine, 1 mmol/L sodium pyruvate, and 50 μmol/L β‐mercaptoethanol in an atmosphere of 5% CO 2 at 37°C, as described previously (Liu, Liu, et al, ). According to the experimental design, the cells were cultured in six‐well plates for 24 hr, and then, primary culture medium was replaced with normal culture medium (RPMI‐1640 medium with 11.1 mmol/L glucose, N), high‐glucose culture medium (RPMI‐1640 medium with 33.3 mmol/L glucose, H), metformin (RPMI‐1640 medium with 33.3 mmol/L glucose and 5 μmol/L metformin, H + Met), chloroquine (RPMI‐1640 medium with 33.3 mmol/L glucose and 5 μmol/L chloroquine, H + CQ), and SIRT1 inhibitor Ex527 (RPMI‐1640 medium with 33.3 mmol/L glucose and 0.1 μmol/L Ex527, H + Ex527), respectively, for another 24‐hr cultivation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…INS‐1 cells (No. CRB‐130515) were purchased from Saiqi Biological Engineering Co., Ltd. (Shanghai, China) and cultured in RPMI‐1640 medium containing 11.1 mmol/L glucose supplemented with 10% fetal bovine serum (FBS), 100 U/ml penicillin, 100 μg/ml streptomycin, 10 mmol/L HEPES, 2 mmol/L l ‐Glutamine, 1 mmol/L sodium pyruvate, and 50 μmol/L β‐mercaptoethanol in an atmosphere of 5% CO 2 at 37°C, as described previously (Liu, Liu, et al, ). According to the experimental design, the cells were cultured in six‐well plates for 24 hr, and then, primary culture medium was replaced with normal culture medium (RPMI‐1640 medium with 11.1 mmol/L glucose, N), high‐glucose culture medium (RPMI‐1640 medium with 33.3 mmol/L glucose, H), metformin (RPMI‐1640 medium with 33.3 mmol/L glucose and 5 μmol/L metformin, H + Met), chloroquine (RPMI‐1640 medium with 33.3 mmol/L glucose and 5 μmol/L chloroquine, H + CQ), and SIRT1 inhibitor Ex527 (RPMI‐1640 medium with 33.3 mmol/L glucose and 0.1 μmol/L Ex527, H + Ex527), respectively, for another 24‐hr cultivation.…”
Section: Methodsmentioning
confidence: 99%
“…The insulin in the supernatant was measured by insulin ELISA kit. The insulin‐releasing stimulation index (ISI) = GSIS/BIS, GSIS, and basal insulin secretion (BIS) are the concentrations of insulin in KRB buffer containing 16.7 and 2.8 mmol/L glucose, respectively (Liu, Liu, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Engineered peptides mimicking extracellular matrix (ECM) increased numerous proliferative indexes and β-cell-specific gene expression in rat INS-1 cells; proposed mediators include integrin receptors and subsequent activation of focal adhesion kinase (FAK) and extracellular signal-regulated kinase (ERK) [44]. …”
Section: Introductionmentioning
confidence: 99%
“…We revealed that RGD and SDKP-displaying M13 nanofiber promoted EPC proliferation through regulation of cyclin D expression. A previous report showed that an M13 phage displaying RGD enhances the proliferative potential of neural progenitor cells and human fibroblasts [27,31], and the interaction between integrin, which is the RGD-binding receptor, and its ligand lead to cell proliferation through focal adhesion kinase-cyclin D pathway [32]. Ac-SDKP augments cell proliferation in endothelial cells and smooth muscle cells [24,33].…”
Section: Discussionmentioning
confidence: 98%